Mutant B3GALT6 in a Multiplex Family: A Dominant Variant Co-Segregated With Moderate Malformations - Shen, Fang; Yang, Yongjia; Zheng, Yu; Tu, Ming; Zhao, Liu; Luo, Zhenqing; Fu, Yuyan; Zhu, Yimin (Frontiers in Genetics, 2022)
Recessive B3GALT6 variants resulting in human diseases have been well documented. However, none of heterozygous B3GALT6 variant causing human disease has been reported. We previously reported on a three-generation, autosomal dominant family with multiple members suffered by radio-ulnar joint limitation, scoliosis, thick vermilion of the both lips and others. In the present study, we performed exome sequencing for the family. Results showed that B3GALT6 as the disease gene for the family, in that, the compound heterozygous pattern (i.e., c.883C>T:p.R295C and c.510_517del:p. L170fs*268) leading to severe consequence, and the heterozygous elongated B3GALT6 variant leading to moderate phenotypes. Functional experiments in vitro were carried out for these two B3GALT6 variants. In consistent to the previous study, the R295C variant leaded to subcellular mis-localization. However, the L170fs*268 leaded to an elongated protein band in Western blot assay, and a normal cellular localization. Due to most of the galactosyltransferase domain was disrupted for the L170fs*268, we propose that the L170fs*268 occupied the normal B3GAT6 protein position and exerts a dominant negative effect.